The interventional effects of PNF training on functional ankle instability in habitually active adults - Weiren Liao; Simao Xu; Rui Wang; Jingzhi Zhang (Frontiers in Public Health, 2026)
Functional ankle instability (FAI) is common among habitually active adults and may lead to recurrent sprains, reduced athletic performance, and long-term joint dysfunction. This randomized controlled trial aimed to compare the clinical efficacy of proprioceptive neuromuscular facilitation (PNF) training with strength-plus-balance training in habitually active adults with FAI. A total of 68 habitually active adults with FAI were randomly assigned to either a PNF training group or a strength-plus-balance training group, both undergoing an 8-week rehabilitation program. Outcome measures were assessed before and after the intervention and included the Cumberland Ankle Instability Tool (CAIT), lower limb stability tests, Star Excursion Balance Test (SEBT), and ankle muscle strength assessments. After 8 weeks, a significant group × time interaction was observed for CAIT scores ( p < 0.001), with improvements from 13.00 ± 2.48 to 24.07 ± 3.53 in the PNF training group and from 13.47 ± 2.45 to 20.13 ± 2.72 in the strength-plus-balance training group. PNF training also produced greater gains in overall balance ability, while strength-plus-balance training was more effective for enhancing ankle inversion strength ( p = 0.039). In conclusion, both rehabilitation programs improved ankle function in habitually active adults with FAI; however, PNF training demonstrated superior improvements in overall balance, whereas strength-plus-balance training was more effective in enhancing ankle inversion strength. These findings may assist clinicians in selecting rehabilitation strategies according to specific therapeutic goals. Clinical Trial Registration ClinicalTrials.gov , registration number: NCT06308809.